The Need to educate foreign workers based on the performance factor in a construction project, especially in a highly populated area in Johor, Malaysia - Mohd Hafizuddin Hakim Zainal; Noorsuhada Md Nor; Soffian Noor Mat Saliah; Siti Isma Hani Ismail; Mohd Faisal Mat Ali; Abdullahi Nafiu Zadawa (Penerbit Universiti Kebangsaan Malaysia, 2023)
The problem of foreign worker is currently increasing due to many factors and has necessitated a comprehensive study to identify the critical factor that leads to the failure of construction projects. Therefore, the objective of this study is to investigate the factors affecting the performance of foreign labour so that the foreign worker can be trained and educated. Methodologically, a total of 68 questionnaires were distributed to respondents at construction sites in four districts of Johor Bahru, Kota Tinggi, Kulai and Pontian in Johor. The selected site was based on the study location, population, design criteria, sample size, sampling frame, sampling method and data collection method. The survey consisted of two sections, Sections A and B. Section A deals with the demographic profile of the respondents. Section B deals with the main factors affecting performance. The data was then analysed using descriptive analysis to determine the mean of the responses. The results show that inadequate health and safety awareness at the worksite is the most important factor affecting the performance of foreign workers. The results also show that the most negative influence of foreign workers is on the construction project. Therefore, the company needs to spend more resources on training the foreign workers. To overcome the problems, the company needs to set and pursue goals to improve the skills of the worker force. This factor is overcome through various strategies such as training foreign labours, monitoring their performance, communicating regularly with the workers and pursuing goals to improve the skills of the workers. The findings of this study can therefore be used to train and educate the foreign worker to perform better in construction projects, especially in heavily populated areas.